MEDICAL STUDENTS’ TIME MANAGEMENT SKILLS AND STRATEGIES IN CONNECTING TO SELF-DIRECTED LEARNING: A QUALITATIVE STUDY - Al-Otaibi, Muneera (PEOPLE: International Journal of Social Sciences, 2019)
Self-directed learning (SDL) is the ability to direct and regulate one’s learning which is crucial to success, and it is associated with life-long learning in the medical profession. However, medical students’ have low readiness for SDL, and therefore, it warrants improvement in the training curricula of medical and post-graduate studies. Several factors influence SDL among medical students and one of the crucial factors is the time management. However, data correlating poor time management with SDL readiness among the medical students in Saudi Arabia has remained underexplored. Thus, exploring the experiences of the medical residents based on Macan’s theory of time management would help understand the importance of time management skills as part of the SDL in Saudi Arabia. Hence, for them to be competent, skilful and self-directed lifelong learner, this study would explore the strategies which could be utilized by the Saudi Medical residents in managing their time by answering the following question: “What strategies do Family Medicine residents use to manage their time to meet the desired learning outcomes?” The study consisted of twenty-five (n=25) participants who qualified the prescribed set of inclusion criteria. Ethical principles included the informed consent, autonomy, confidentiality, privacy, and anonymity were ensured throughout the entire research. The emergent themes that were generated from the focus group discussions (FGD) were observed to be associated with the widely known model of Macan’ Time Management (1994). The management process involved four steps which included the planning, organizing, directing and controlling of time which reflected in the experiences shared by the family medicine residents in achieving the desired learning outcomes through SDL. This study concluded that there would be positive outcomes if the tested strategies of time management are used to train the medical residents.